2010
DOI: 10.1053/j.gastro.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Regulates Transforming Growth Factor β1 Production Through the Generation of Reactive Oxygen Species in a Nuclear Factor κB–Dependent Manner

Abstract: Background & Aims-The generation of oxidative stress and TGF-β1 production play important roles in liver fibrogenesis. We have previously shown that HCV increases hepatocyte TGF-β1 expression. However, the mechanisms by which this induction occurs have not been well studied. We explored the possibility that HCV infection regulates TGF-β1 expression through generation of reactive oxygen species (ROS), which act through one or more of the p38 MAPK, ERK, JNK, and NFκB signaling pathways to induce TGF-β1 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
160
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 35 publications
14
160
1
1
Order By: Relevance
“…S6 D and E), suggesting that the function of HCV in regulating E-cadherin expression and inducing EMT relies, at least partially, on TGF-β activation. The induction of TGF-β by HCV has been previously reported (25). In addition, treatment of cells with E-cadherin blocking antibody had no effect on VIM and FN1 expression (Fig.…”
Section: Hcv Infection Represses E-cadherin Expression and Induces Emtmentioning
confidence: 69%
“…S6 D and E), suggesting that the function of HCV in regulating E-cadherin expression and inducing EMT relies, at least partially, on TGF-β activation. The induction of TGF-β by HCV has been previously reported (25). In addition, treatment of cells with E-cadherin blocking antibody had no effect on VIM and FN1 expression (Fig.…”
Section: Hcv Infection Represses E-cadherin Expression and Induces Emtmentioning
confidence: 69%
“…The multiplicity of infection of JFH1 in our experiments was 0.2. We found that JFH1-infected Huh7.5.1 cells were about 50% infected at 48 h and at least 95% infected at day 6 by HCV core immunofluorescence staining both in this study and in our previous report (30). (B) Full-length GT1a, GT1b, GT3a, or GT3b NS5A; NS4B constructs; or the empty vector control, pCAGGS-V5/His, was cotransfected with pISRE-luc and pRL-TK into Huh7.…”
Section: Resultsmentioning
confidence: 95%
“…The Huh7.5.1 cells were infected with HCV JFH1 as previously described (30,31,45). The infectious GT1 and GT3 NS5A recombinant viruses were produced from recombinant DNA constructs, as previously reported (39).…”
Section: Cell Cultures and Infectious Virusesmentioning
confidence: 99%
“…Proteins were obtained, separated, and transferred to nitrocellulose membranes as reported previously (26,27). The target proteins were detected with the following specific primary antibodies: mouse anti-HCV core protein (C7-50; Fisher Scientific); mouse anti-actin, rabbit anti-EFTUD2, rabbit anti-RIG-I, rabbit anti-MDA5, rabbit anti-TBK1, rabbit anti-MxA1, and rabbit anti-OAS1 (Sigma Life Science and Biochemicals); and rabbit anti-IRF3 and anti-phospho-IRF-3 (Ser396) (Cell Signaling Technology).…”
Section: Western Blottingmentioning
confidence: 99%